The Effectiveness of Utilization of Public Facilities as Public Open Space - Azizah, Ismi; Winanda, Gayu; Nariyah, Hery (Jurnal Polisci, 2025)
Background. Public open spaces, such as city parks and other public facilities, play a crucial role in supporting social development, especially amid increasing urbanization. Aims. The purpose of this study is to assess the effectivenessofutilizing public facilities as public open spaces, identify various factors that hinder effectiveness, and make efforts to improve their efficacy. The theory employed in this research is the theory of effectiveness, as proposed by James L. Gibson, which comprises five indicators of effectiveness: productivity, quality, efficiency, flexibility,andsatisfaction. Methods. The method used in this research is qualitative in a descriptive approach to analyze the effectiveness of public open space utilization based on aspects of design, accessibility, and community participation. Result. The results showed that although the Cirebon City government has tried to meet the needs of public open space, many facilities are not functioning optimally. Conclusion. The findings suggest that revitalizing city parks is crucial for enhancing both social and economic functions, as well as providing space for community activities. Implementation. Therefore, the results of this study are expected to serve as a guide for more inclusive and sustainable policy planning in the development of public open spaces in the city of Cirebon.